ANALISIS KESALAHAN MAHASISWA PERBANKAN SYARIAH IAI IBRAHIMY GENTENG DALAM MENYELESAIKAN SOAL EKONOMETRIK BERDASARKAN MODEL KASTOLAN - Anis Hidayati MS; Nurul Hidayah (NATUJA: Jurnal Ekonomi Syariah, 2021)
This study was conducted to analyze student errors in working on econometric questions in order to facilitate the handling. The analysis used is the theory of error analysis according to Kastolan. This research was conducted using qualitative research methods with a case study approach. This research was conducted at the IAI Ibrahimy Genteng campus in Banyuwangi, on Wednesday, June 19, 2019. The research subjects in this study were students of Islamic Banking class 2006. Data were collected by observation, interviews and documentation. As for the conclusions from the research on the errors of Kastolan's theory by students, it can be seen that conceptual errors occur because students do not understand the concept of the classical assumption test. procedural errors occur as a result of a lack of understanding of the concept of the learning material, resulting in errors in carrying out the steps in working on/answering the questions given. While in technical errors, students make this error because of lack of accuracy in performing arithmetic operations. The factors that cause conceptual errors made by students are due to the lack of student knowledge about the concept of regression and classical assumptions. Factors causing procedural errors made by students are difficulties in manipulating the steps and confusion in determining the steps for working on the classical assumption test. Furthermore, the factor causing technical errors made by students is because students do not pay attention to the available time so that at the end of the exam the time is up without being able to re-check their work.